2022
DOI: 10.1002/alz.12724
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aβ42/40 ratio, p‐tau181, GFAP, and NfL across the Alzheimer's disease continuum: A cross‐sectional and longitudinal study in the AIBL cohort

Abstract: Introduction: Plasma amyloid beta (Aβ)1-42/Aβ1-40 ratio, phosphorylated-tau181 (p-tau181), glial fibrillary acidic protein (GFAP), and neurofilament light (NfL) are putative blood biomarkers for Alzheimer's disease (AD). However, head-to-head Pratishtha Chatterjee and Steve Pedrini contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
52
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 55 publications
8
52
2
Order By: Relevance
“…Additionally, MAO-B PET signal has also been reported to be significantly higher at 6 months than at 8–15 months or 18–24 months in APPswe mice [ 65 ]. In contrast, plasma GFAP has been observed to increase along the AD continuum [ 12, 13 ]. Together, these observations suggest that the low to moderate strength associations observed between plasma GFAP and 18 F-SMBT-1 PET signal within the current study could also be attributed to the study participant status within the AD continuum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, MAO-B PET signal has also been reported to be significantly higher at 6 months than at 8–15 months or 18–24 months in APPswe mice [ 65 ]. In contrast, plasma GFAP has been observed to increase along the AD continuum [ 12, 13 ]. Together, these observations suggest that the low to moderate strength associations observed between plasma GFAP and 18 F-SMBT-1 PET signal within the current study could also be attributed to the study participant status within the AD continuum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that reactive astrocytes release GFAP into blood via astrocyte end-feet encompassing brain capillaries [ 13 ]. Indeed, plasma GFAP levels are elevated in individuals with high Aβ in the brain (Aβ+) compared to those with low Aβ in the brain (Aβ–) [ 6, 7, 14, 15 ]; and have demonstrated high accuracy in differentiating Aβ+ from Aβ–participants, as assessed by PET, along the AD continuum [ 12 ]. Furthermore, plasma GFAP has a higher accuracy than CSF GFAP in distinguishing Aβ+ from Aβ–participants [ 8 ] and can predict progression from the mild cognitive impaired stage (MCI; prodromal AD) to AD [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the rapidly developing research on plasma biomarkers, studies investigating longitudinal change remain limited. Chatterjee et al reported that plasma measures of Aβ 42 /Aβ 40 , tau phosphorylated at threonine 181 (p-tau181), and glial fibrillary acidic protein (GFAP) change more rapidly among individuals with mild cognitive impairment (MCI) compared to cognitively normal individuals [8]. O’Connor et al found that longitudinal trajectories of plasma neurofilament light chain (NfL) and p-tau181 among autosomal dominant AD mutation carriers started diverging from trajectories observed for non-carriers at about 16–17 years prior to estimated symptom onset [9].…”
Section: Introductionmentioning
confidence: 99%
“…Only NfL levels were found to be affected by renal function in A + , but not for p-tau181. A possible explanation is that p-tau181 is a more specific biomarker for AD pathology compared with NfL ( Chatterjee et al, 2022 ; Sarto et al, 2022 ), the impact of renal function on p-tau181 levels may be weaker in A + . This was consistent with our findings that the AUC and sensitivity of p-tau181 were higher than NfL.…”
Section: Discussionmentioning
confidence: 99%